Between Freedom and Fixity: Artistic Reflections on Composition and Improvisation - Shay, Ilya Ziblat (Leiden Universiteit van Leiden, 2019)
Between Freedom and Fixity: Artistic Reflections on Composition and Improvisation is Ilya Ziblat Shay's practice-based research project. Four of Ziblat's compositions are discussed as musical models that integrate freedom and fixity, presenting (musically) tangible forms of the two concepts. Different approaches to notation, improvisation, performance, and electronic music are presented, and the research also draws on extra-musical notions in order to extend the direct practice-based context. By exploring the possible functions of freedom and fixity as they exist in composition this research aims to be relevant not only to musicians and scholars but also to listeners in general.
PhD dissertation for docARTES, Universiteit van Leiden
Keywords: Composing; Improvisation; Artistic research